A study of relationship between emotional intelligence towards academic achievement in public university from northern region / Azlyantiny Mohammad ...[et al.] - Mohammad, Azlyantiny; Jamaludin, Mohd Fazil; Mohd Helmi, Mohd Firdaus (2013)
This study attempts to highlight the issues related to Emotional Intelligence and Academic Achievement. The populations are chosen from students at Public University from Northern region. A few studies conducted have shown that emotional intelligence have a significant relationship in increasing the student’s academic achievement (Koh Bee Hong, 1999; Adeyemo, 2007; Dubey, 2012; Nwadinigwe and Azuka-Obieke, 2012; Bradshaw, 2008). This is also agreed by the former Education Minister of Malaysia, in his interview with New Strait Times (1999) reiterated the important of a holistic education and said that entry to boarding schools will be based not only on academic excellence, but also on emotional intelligence as cited in Koh (1999) study. Researcher believes that emotional intelligence is also important to be implemented towards universities student as well. The objective of this study is to find a relationship between dimension of emotional intelligence (self-awareness, self-regulation, motivation, empathy and social skills) and academic achievement and measure to what extent do the dimensions of emotional intelligence contribute towards academic achievement. The dimensions were measured using questionnaires from other researcher. Quota sampling is used to determine the number of population. Three hundred questionnaires will be distributed to the students from public.university in the northern region. Data will be explored using SPSS 19.0 and it is hoped from the result derived it will somehow provide some kind of preliminary assessment and feedback of the emotional intelligence of students and how it relates with the student’s achievement. On the other hand, it is hoped that the result will provide information of the need to focus on five dimensions of emotional intelligence in helping the students to succeed in their academic achievement. Last but not least it is hopeful that the findings will create interest and provide an avenue for the development of future research in the same or related area.